Shoaling develops with age in Zebrafish (Danio rerio) - Buske, Christine (2010)
The biological mechanisms of human social behavior are complex. Animal models may facilitate the understanding of these mechanisms and may help one to develop treatment strategies for abnormal human social behavior, a core symptom in numerous clinical conditions. The zebrafish is perhaps the most social vertebrate among commonly used laboratory species. Given its practical features and the numerous genetic tools developed for it, it should be a promising tool. Zebrafish shoal, i.e. form tight multimember groups, but the ontogenesis of this behavior has not been described. Analyzing the development of shoaling is a step towards discovering the mechanisms of this behavior. Here we study age-dependent changes of shoaling in zebrafish from day 7 post fertilization to over 5 months of age by measuring the distance between all pairs of fish in freely swimming groups of ten subjects. Our longitudinal (repeated measure within subject) and cross sectional (non-repeated measure between subject) analyses both demonstrated a significant increase of shoaling with age (decreased distance between shoal members). Given the sophisticated genetic and developmental biology methods already available for zebrafish, we argue that our behavioral results open a new avenue towards the understanding of the development of vertebrate social behavior and of its mechanisms and abnormalities.